The Role of the Young Generation in Increasing Knowledge of Islamic Family Law to Overcome Bullying Problems at SMK PUI Jatibarang, Indramayu, West Java - Elya Nurjannah; Muhil Mubarok (International Research and Development for Human Beings (IRDH), 2025)
Bullying among students is a serious phenomenon that can damage the psychological, social, and moral development of young people. Bullying not only causes trauma for victims but also disrupts the quality of education and the overall school environment. From the perspective of Islamic family law, moral values ​​such as compassion, responsibility, and justice are important guidelines in preventing violent behavior among children and adolescents. A community service seminar held in August 2025 at SMK PUI Jatibarang Indramayu aimed to increase the younger generation's knowledge of Islamic family law and its role in addressing bullying issues. This activity used interactive lectures, group discussions, and case simulations to explain the rights and obligations of family members, the role of parents, and the application of Islamic values ​​in social life. The results of the activity showed that Islamic family law literacy can serve as a preventive basis for students to develop noble character, respect differences, and avoid bullying behavior. The younger generation realized that acts of violence not only violate social norms and positive law but also contradict Islamic principles that uphold human dignity. With increased understanding of Islamic family law, it is hoped that a more harmonious, safe, and bullying-free educational environment will be created.